Susceptibilidade de Haematobia irritans (Linnaeus, 1758) (Diptera: Muscidae) ao inibidor de desenvolvimento de insetos, diflubenzuron, em Uberlândia-MG - Silva, Juliana Junqueira da (2001)
Haematobia irritans is one of the most important cattle pest. The wide use of conventional insecticides to control this pest has resulted in arising of resistant populations to the majority of the insecticides. Apart from this, alternative means of control, which are not harmful to humans and other animal’s health or to the environment have been sought. Diflubenzuron, an insect growth regulator, has been studied as an alternative in the control of various pests, including the horn fly. This study had three objectives: to verify H. irritans susceptibility to different concentrations of diflubenzuron in Uberlândia - MG, to determine the lethal concentrations of the product to 50% and 95% (LC50 and LC95) of the fly and to verify the actions of the product in its different immature stages. Experiments were done using eggs and larvae obtained from adult flies from cattle fields and maintained in medium containing dung + diflubenzuron (treated medium) and medium containing only dung (control medium). Concentrations of 300 ppb, 100 ppb and 50 ppb were lethal to 100% of the population. Pupae larvae shaped appeared, which increased in numbers with the reduction of the concentration of the product to 35 ppb, from the concentration of 100 ppb on. The emergence of imagoes was observed at concentration 35 ppb and increased in number with the reduction of diflubenzuron concentration in the breeding medium. The values of LC50, LC95, and the linear angular coeficient were 25.521 ± 1.011 ppb; 34.650 ± 1.021 ppb and 12.720 ± 1.096, respectively. The high value of the angular coeficient of regression line and the susceptibility of H. irritans to low diflubenzuron concentrations suggest that there is a high susceptibility of the tested population to this growth regulator. The third larvae stage were shown to be the most susceptible to diflubenzuron in sublethal concentration.